Plant Community Distinctiveness of Peripheral Zone of Nongkhyllem Wildlife Sanctuary, Meghalaya, North-East India - Bhuyan, S. I.; Laskar, I. (Indian Forester, 2022)
Present study was conducted during 2017-2018 in Nongkhyllem Wildlife Sanctuary, Meghalaya lies between 25Â°45’-26Â°00’ N latitude and 91Â°45’92Â°00’ E longitude. Data was collected and analyzed using the standard methodology. A total of 72 plant species were recorded in the study. Out of these 18 tree species (belongs to 13 genera and 11 families) of angiosperm were recorded and similarly 30 species of shrubs (28 genera and 21 families) and 24 species of herbs (19 genera and 16 families). The Margalef’s diversity index for trees, shrubs and herbs were 10.00, 11.12 and 8.64 respectively and Shannon and Weiner diversity index were 2.67, 3.11 and 2.98 respectively for trees, shrubs and herbs whereas for Simpson Dominance index for trees, shrubs and herbs were 0.008, 0.003 and 0.005 respectively. Evenness for trees, shrubs and herbs were 0.92, 0.91 and 0.93 respectively. Knowledge of forest characteristics is an important factor for the formulation of conservation practices.